South Africa. Two views of Separate Development: Safeguarding the nations of South Africa. By S. Pienaar. - Old fallacies with a new look: ignoring the Africans. By A. Sampson. With a forew. by Ph. Mason (Oxford University Press, 1960)
Issued under the auspices of the Institute of Race Relations.